CREATION OF OPEN INFORMATION-EDUCATION ENVIRONMENT AND IMPROVEMENT OF USE COMPETENCES FOR BIOLOGY TEACHERS IN GENERAL SECONDARY EDUCATION INSTITUTIONS - Khushnud Nurmetov (Web of Journals Publishing, 2024)
In this article, continuity, consistency, improvement of natural scientific literacy in the field of pedagogical education for general secondary educational institutions, organization and management of the educational process at a high level, open information and education in improving the efficiency of the qualifications of biology teachers information on creating an environment and improving usage indicators is covered.
Keywords: Multimedia, GIF animation, integration, open information and educational environment, information and communication technologies, pedagogical technologies, interactive technologies, distance learning, didactic, technological, organizational and communicative competencies.